2012
DOI: 10.1007/s00402-012-1498-3
|View full text |Cite
|
Sign up to set email alerts
|

Normal sagittal of the anterior cruciate ligament can be reproduced using accessory anteromedial portal technique: a magnetic resonance imaging study

Abstract: Level III, diagnostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Contradictory to the previous findings, TI technique placed femoral aperture at a significantly shallower position than the TT technique as measured by Harner method [ 77 ] on radiography in 2 studies (92 participants) [ 28 , 46 ] (Additional file 6 ). A consistent finding was demonstrated in one study (30 patients) [ 20 ], where the placed femoral aperture screw head of TI technique was at a significantly shallower position than that of the TT technique as measured by the quadrant method on radiography. Also, in one study (12 specimens) [ 65 ], TI technique placed femoral aperture anterior margin at a significantly shallower position than the TT technique as measured by Aglietti method [ 77 ] directly on specimen.…”
Section: Resultssupporting
confidence: 81%
“…Contradictory to the previous findings, TI technique placed femoral aperture at a significantly shallower position than the TT technique as measured by Harner method [ 77 ] on radiography in 2 studies (92 participants) [ 28 , 46 ] (Additional file 6 ). A consistent finding was demonstrated in one study (30 patients) [ 20 ], where the placed femoral aperture screw head of TI technique was at a significantly shallower position than that of the TT technique as measured by the quadrant method on radiography. Also, in one study (12 specimens) [ 65 ], TI technique placed femoral aperture anterior margin at a significantly shallower position than the TT technique as measured by Aglietti method [ 77 ] directly on specimen.…”
Section: Resultssupporting
confidence: 81%
“…77 Postoperative cross-sectional imaging was also frequently used to compare tunnel characteristics after ACL reconstruction. 11,18,31,60 Three magnetic resonance imaging (MRI) studies demonstrated that femoral tunnels drilled independently were more oblique in the coronal and sagittal planes as compared with TT femoral tunnels. 11,18,31 There was also evidence that the aperture of the femoral tunnel was closer to the center of the anatomic footprint when independent drilling was used.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…11,18,31,60 Three magnetic resonance imaging (MRI) studies demonstrated that femoral tunnels drilled independently were more oblique in the coronal and sagittal planes as compared with TT femoral tunnels. 11,18,31 There was also evidence that the aperture of the femoral tunnel was closer to the center of the anatomic footprint when independent drilling was used. 1,11,18,60 Studies in a motion analysis laboratory have also been performed.…”
Section: In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation